Вступительное слово - Александр Сергеевич Огнев (Психология. Журнал Высшей школы экономики, 2014)
Now it is difficult to imagine that 15-20 years ago using the term “subject” in psychology seemed unproductive to many practicing psychologists. In their view, this concept was more suitable for describing the philosophical fundamentals of human existence, at best it could be applied in methodology of psychological research. But in many theoretical works of that period the discussion of psychological aspects of subjectivity and human nature for the most part dealt with clarifying the views of S.L.Rubinstein, the specifics of interpretations of the subject in the works of B.F.Lomov and prospects for using in interdisciplinary theory of knowledge the ideas V.A.Lectorskiy on the multilevel cognitive activity of interacting individual and collective subjects.The unhurried course of the purely academic consideration of the subject nature of man was radically disrupted by a series of studies carried out under the leadership of V.A.Petrovskiy aimed at identifying such forms of activity, in which the determining beginning of man was presented explicitly. From the very beginning the research in this field has combined respect for a rich philosophical tradition of describing human subjectivity, the deep theoretical understanding of the facts of its manifestations obtained in the experimental study, and the focus on the practical application of new scientific knowledge in the psychological and pedagogical practice. A keen interest in sometimes paradoxical manifestations of supra-situational activity, and the obvious heuristicity of the new theory soon led to literally an explosion of works that combined detailed study and pragmatic use of the phenomenon of human subjectivity. The paradigm of subjectivity in psychology in the subsequent period of development incorporated both the organic components of V.Petrovskiy’s idea of the multisubject nature of the individual, methods of the virtual, reflected and transformed subjectivity developed by his school, and the subject-genetic approach to the organization of various kinds of psychological and pedagogical practices. The scientific value and practical significance of the multisubject interpretation of the personality as the source and the cause of own activity led to the consolidation of both academic and applied components of psychology into a single science of personality — personology. The thematic collection presented in this issue includes the latest research showing how the idea of subjectivity can be used as a productive base for combining science and practice. Their non-triviality in scientific terms and a high practical significance make a clear evidence of the vitality of the subject paradigm in the study of the human personality and in the work to improve human life. The article by M.A.Schukina The Subject Approach to Self-development of Personality: Possibilities of a Theoretical Understanding and Empirical Study shows the validity of modes of general subjectivity and subjectivity of development in terms of both theoretical and empirical research. The author focuses on ways of a theoretical description and empirical studies of the concepts of personality on the ways of own development and of factors influencing the person’s choice of life strategy. The article by T.Gavrilova and S.Popova Success and the Contents of the Subject’s Coping with Auto Mortal Anxiety presents results of the study and success of various ways to overcome human fear of personal death. The authors show gender-specific efforts of young men and women to cope with this type of anxiety and provide a comparative analysis of the degree of success of the various strategies being demonstrated in the coping behavior. The article by I.Vachkov Polysubject Cooperation in Education Environment describes the methodological foundations of the author's approach to the polysubject interaction as one of the kinds of pedagogical interaction. The article mentions the criterion signs of polysubjectivity, and a typology of communities formed during different types of interaction. In the article by A.S.Ognev and E.V.Likhachev Practice of Implementing Positively Oriented Subject Genesis in Higher Educationthe essence of the subject-genetic approach to psychological and pedagogical practices is revealed. The authors show some specific ways of its implementation in the higher education system using an example of the educational module Life Navigation®.